Value of Fragmented QRS Complex on 12-lead ECG as A Valuable Marker of Myocardial Damage of CAD Patients - andrico tobing; Anggia Chairuddin Lubis; Edison Bun; Harris Hasan (Jurnal Kardiologi Indonesia, 2019)
Background: Presence of Fragmented QRS (fQRS) on a 12-lead Electrocardiogram (ECG) was associated with various cardiac diseases. This phenomenon could represent as an electrical disruption of conduction system following myocardial damage due to coronary artery disease (CAD). We aimed to investigate the value of fQRS to detect the myocardial scar as detected by SPECT Myocardial Perfusion Imaging (MPI). Methods: A cross-sectional study of patients with clinical diagnosis of CAD who underwent Cardiac SPECT. The fQRS defined as morphologies of QRS wave (<120 ms), which included an additional R wave (R’), notching in the nadir of S wave, or >1 R’ (fragmentation) in 2 contiguous leads, corresponding to a major coronary artery territory. Pathological Q wave, paced rhythm, typical right or left bundle branch block pattern with QRS duration of ≥ 120 ms were excluded. MPI was interpreted by visual analysis and semi-quantitative scores on 17-segment assessment according to standard nomenclature. Results: Total of 72 patients (49 males, mean age 54.7 ± 9.8 years). fQRS was found in 46 patients (64%). The frequency of myocardial scar was significantly higher in patients with fQRS (89% vs. 15%, p<0.05). Sensitivity, specificity, positive and negative predictive value of fQRS for any of myocardial scar as detected by SPECT analysis were 91%, 81%, 89%, and 84%, respectively. From regional scar analysis, fQRS has sensitivity and specificity of 87% and 90% for anterior wall, 76% and 80% for inferior wall, 73% and 79% for lateral wall. LVEF was significantly lower in patients with fQRS (36.9±2.1 vs. 53.2±2.2, p< 0.05). Conclusion: The fragmented QRS could serve as a novel ECG marker to detect and localize the myocardial damage in CAD patients. Regional fQRS patterns denote the presence of regional myocardial scar and are a valuable diagnostic marker of CAD with good sensitivity and specificity. Keywords: fragmented QRS, SPECT